Risk Factors Related to the in-hospital Evolution of Patients with ST-segment Elevation Acute Coronary Syndrome - Chen Shang; Héctor Pérez Assef; Marlene Ferrer Arrocha (Revista Finlay, 2023)
Background: acute coronary syndrome with ST segment elevation is one of the main reasons for consultation and admissions to emergency services. Its clinical course and prognosis can be modified by various factors. Objective: to analyze the risk factors related to the in-hospital evolution of patients with ST-segment elevation acute coronary syndrome admitted to the coronary intensive care unit of the Institute of Cardiology and Cardiovascular Surgery. Methods: a cross-sectional analytical study was carried out that included 99 patients with a diagnosis of STEACS admitted to the coronary care unit of the Institute of Cardiology and Cardiovascular Surgery, from June 2018 to June 2019. Sociodemographic variables were collected, clinical and angiographic. The response variables were complications and death from cardiovascular causes that occurred during hospital admission. The frequency distribution was analyzed, the Chi Square test was performed and the mean differences for independent samples were used. Results: patients older than 60 years predominated, with a mean age of 63 years and the male sex. Arterial hypertension was the most frequent risk factor, followed by smoking. It was found that the Killip Kimball III-IV classification had a strong association with an unfavorable evolution with an OR of 41.50 (p=0.000), followed by previous acute myocardial infarction OR of 3.25 (p=0.03). Conclusions: the Killip Kimball II-IV classification, the Grace scale of moderate to high risk, and creatinine values had a greater association with unfavorable in-hospital evolution.